Potential nutritional countermeasures to exerciseinduced immunosuppression - Niemann, D. C. (Medicina Sportiva, 2003)
In contrast to moderate physical activity, prolonged and intensive exertion causes numerous changes in immunity that reflect physiologic stress and suppression, and an increased risk of upper respiratory tract infection. In that multiple enzymes in immune cells require the presence of micronutrients, attempts have been made to alter changes in immunity following heavy exertion through use of nutritional supplements, primarily zinc, dietary fat, vitamin C and other antioxidants, glutamine, and carbohydrate. Except for carbohydrate supplementation, none of these nutrients has emerged as an effective countermeasure to exercise-induced immunosuppression. Data from several studies of endurance athletes suggest that carbohydrate compared to placebo ingestion is associated with an attenuated cortisol, growth hormone, and epinephrine response to heavy exertion, fewer perturbations in blood immune cell counts, lower granulocyte and monocyte phagocytosis and oxidative burst activity, and a diminished pro- and anti-inflammatory cytokine response. Overall, the hormonal and immune responses to carbohydrate compared to placebo ingestion suggest that physiologic stress is diminished, although clinical significance awaits further research.